Attitude towards household solid waste management in students of a private university - Domínguez Del Águila, Danny (2021)
Descriptive-comparative research with the objective of describing the attitude towards the management of household solid waste in students at a private university in the city of Lima. Study in a random sample, the collaborators participated after informed consent on the objective of the study framed in the PEQI environmental perceived index focused on solid waste management. The data was obtained using the Osgood-type attitude scale – MAARS-2019, with an omega index of 0.956 to 0.976 whose validity and reliability is significant. The results indicate that level of perceived index is 4.605, indicating as an attitude that tends towards the positive direction in the studied population towards the management of household solid waste, thus guiding the favorable diagnosis to achieve environmental behaviors to reduce its environmental impact. That has been observed in the generation of greenhouse gases associated with climate change and public health.